Some key points in the debate on the content and concept of human rights - Chacón Mata, Alfonso (2025)
Through this article it is intended to emphasize the particularities of the content of human rights at a conceptual level. Different problems faced by the concept will be analyzed, ranging from the various meanings or conceptions that human rights have to be defined; the contradictions inherent in their self-executability due to lack of specificity to trying to find keys that clarify the concept in practice.  Therefore, it is not feasible to think what is the proper content of human rights, if there are no tools to help in this task.